IMPLEMENTASI KEBIJAKAN PAJAK PERTAMBAHAN NILAI DALAM KONFLIK PENYERAHAN JASA DI KAWASAN FREE TRADE ZONE - Khansa Salsabila; Fatma Ulfatun Najicha (Indonesian State Law Review, 2022)
Free Trade Zone area has its own rules in tax collection, including the delivery of taxable service. However, in the implementation of the policy in tax collection, there are still errors that cause conflicts between taxpayers and tax authorities. For example, such as the article in the Regulation of the Minister of Finance Number PMK-62/PMK.03.2012 which gives rise to multiple interpretations for taxpayers. The author will describe the implementation of correct policies in taxable service conflicts in the free trade zone using empirical juridical and normative juridical research methods. In the law there is the principle of lex posterior derogat legi priori which means that the new law (norm/legal rule) nullifies the validity of the old law (norm/rule of law). In addition, the use of the principle of legal fiction which assumes that when a statutory regulation has been promulgated, at that time everyone is considered to know (presumption iures de iure) and the provisions are binding. Thus, the taxpayer should be aware of the latest regulations regarding tax collections that he must pay. In this case, taxpayers can use the latest regulation, Regulation of the Minister of Finance PMK Number 171/PMK.03/2017.